Microwave Assisted Green Synthesis of Benzimidazole Derivatives and Evaluation of Their Anticonvulsant Activity - Sahoo, Biswa M.; Banik, Bimal Krishna; Mazaharunnisa; Rao, Naidu Srinivasa; Raju, Bodapati (Current Microwave Chemistry, 2019)
Background: Benzimidazole is the fused heterocyclic aromatic compound. It is an essential pharmacophore and privileged structure for the development of new drug molecules. These are bioactive molecules present in various anthelmintic drugs such as albendazole, mebendazole, parbendazole, triclabendazole etc. Methods: Benzimidazole derivatives are synthesized by reaction between orthophenylene diamine and anthranillic acid followed by acetylation in the presence of acetic anhydride. Finally, the acetylated products undergo Claisen-Schimdt condensation with various substituted benzaldehydes to produce corresponding benzimidazole derivatives or chalcones. Both conventional and microwave irradiation technology are followed to get the titled compounds. The titled compounds are screened for their anticonvulsant and neurotoxicity activity. Results: By the help of microwave synthesis, the yield of product was increased in less reaction time. So, it follows Green chemistry approach by making above reactions eco-friendly. Some of the compounds exhibited significant anticonvulsant activity as compared to standard drug. Conclusion: In the present investigation, we have synthesized novel benzimdazole derivatives with chalone moiety to improve the biological activity. The compounds were obtained under microwave reaction with high yield in a short reaction time.
Keywords: green synthesis